Acute coronary syndromes related to bio-climate in a Mediterranean area. The case of Ierapetra, Crete Island, Greece - Nastos, P. T.; Giaouzaki, K. N.; Kampanis, N. A.; Matzarakis, A. (International Journal of Environmental Health Research, 2013)
The occurrence of non-fatal acute coronary syndromes (ACS) is examined in relation with the local bioclimatic conditions in the Ierapetra area, in the southernmost part of Crete Island, Greece, during the period 2004-2007. Daily ACS counts and corresponding meteorological parameters, such as maximum and minimum air temperature, relative humidity, wind speed and cloudiness, were analyzed. Besides, the daily values of the human thermal index, physiologically equivalent temperature (PET) was evaluated. Pearson's 2 test and generalized linear models (GLM) with Poisson distribution were applied. The ACS syndromes present a multiple variation within the year, with the primary maximum in August and the secondary in May, while relative high ACS frequencies exist in early winter time. The impact of the weather variability on the ACS incidence is not statistically significant (C.L. 95%). © 2013 Copyright Taylor and Francis Group, LLC.
Keywords: acute coronary syndrome; Acute coronary syndromes; acute heart infarction; Adult; Aegean Islands; Aged; Aged, 80 and over; air temperature; Angina, Unstable; article; Bioclimatic conditions; bioclimatology; Chi-Square Distribution; Child; Climate; Climate change; cloud; Cloud cover; Crete; Crete Island; Female; frequency analysis; Generalized Linear Models; Greece; human; Humans; humidity; Ierapetra; Incidence; Linear Models; linearity; major clinical study; Male; meteorological phenomena; Meteorology; Middle Aged; Myocardial Infarction; numerical model; Poisson distribution; Relative humidity; seasonal variation; Seasons; Southern Europe; temperature; unstable angina pectoris; velocity; Weather; wind; wind velocity; winter